IMF Staff papers : Volume 17 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1970)
The purpose of this paper is to provide a statistical measure of past changes in effective exchange rates of major currencies over a continuous recent period and to discuss briefly the significance of the results shown. Particular attention is paid to the relationship between the indirect influence on effective exchange rates resulting from exchange adjustments of other currencies and the direct influence resulting from adjustments in the given currency. The weights to be applied to movements in each country's numeraire exchange rate in its impact on other countries' effective rates could be determined by a few criteria. The comparisons suggest that the effective appreciation of the US dollar in the period since European currencies attained convertibility did not result from any general devaluation bias in the adjustment of par values. Judged by the impact of competitors' par value changes on industrial countries generally, there has been no such general devaluation bias. The effective appreciation for the United States since 1959 reflects rather the orientation of its trade, and particularly its large trade with Canada.